2018
DOI: 10.1002/ep.13026
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Tamarix hispida Biochar by Lanthanum Chloride for Enhanced Fluoride Adsorption from Synthetic and Real Wastewater

Abstract: The purpose of this research was the preparation of Tamarix hispida biochar during a pyrolysis process and then improvement its fluoride adsorption capacity by lanthanum chloride. The biochar powder was amended by lanthanum during a precipitation‐oxidation method to make biochar–lanthanum (biochar–La). Adsorbent characteristics of the fresh and fluoride loaded biochar–La were determined by using Fourier‐transform infrared spectroscopy spectrometer, Brunauer–Emmett–Teller, pH of zero point charge, energy‐disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The other is the loading of carbon-based materials, in which aluminum or other metals can be loaded on carbon-based materials. Biochar loading has been widely reported recently (Habibi et al 2018;Zhang et al 2019a;Yan et al 2021). Biochar is a product obtained by the pyrolysis of biomass such as crop straw, rice husk, tea residue, bone, vegetables and other agricultural wastes under high temperature (generally ,700°C) in anoxic or anaerobic environment (Guo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The other is the loading of carbon-based materials, in which aluminum or other metals can be loaded on carbon-based materials. Biochar loading has been widely reported recently (Habibi et al 2018;Zhang et al 2019a;Yan et al 2021). Biochar is a product obtained by the pyrolysis of biomass such as crop straw, rice husk, tea residue, bone, vegetables and other agricultural wastes under high temperature (generally ,700°C) in anoxic or anaerobic environment (Guo et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of ionic exchange with F − is higher and the affinity is stronger. Habibi et al (2019 ) modified woody BC with LaCl 3 and showed that the maximum adsorption capacity of 164.23 mg/g and adsorption equilibrium could be reached within 30 min. They concluded that H + in functional groups such as carboxyl and sulfate groups on the surface of BC may exchange with La 3+ ions.…”
Section: New Composite Adsorbents Obtained From Metal Modificationmentioning
confidence: 99%
“…Since the surface charge of biochar materials prepared from plant material classes is usually negative, the same as for fluoride, and the electrostatic effect is weak, which prevents the effective adsorption of fluoride [23], the development of effective modification methods to enhance the adsorption efficacy of fluoride is of great significance for biochar research. The main modification methods currently used involve metal modification [24]; one such example shows that the rare earth metal lanthanum (La) has a high affinity for fluoride [25]. However, the high price of lanthanum limits its practical application, so loading lanthanum on inexpensive materials may be an economical way to reduce the amount of lanthanum required while maintaining a high adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%